PENUNDAAN BERLARUT (UNDUE DELAY) PENANGANAN PERKARA DUGAAN TINDAK PIDANA PENGHALANG-HALANGAN DAN KEKERASAN KEPADA KERJA PERS: SEBUAH TINJAUAN KRITIS - M. Rizki Yudha Prawira, M. Rizki Yudha Prawira (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2024)
Guaranteeing rights to press freedom does not only lie in the existence of laws and regulations to protect it and institutions that specifically implement it, but also in certainty in law enforcement. One of the components of press protection is legal certainty in the investigation and/or inquiry process by the Indonesian National Police (Polri). One of the problems in the law enforcement process is protracted delays, also known as undue delays. According to the Ombudsman Regulation No. 26 of 2017, Article 11 regulates that one form of maladministration is protracted delays where services are provided beyond the time quality standards of the service promise. Based on a report by the Legal Aid Center for the Press, from 2020 to 2022, there were nine cases of suspected criminal acts against the Press that were suspected of undue delay or protracted processes. Based on the report and the pattern of these cases, five were physical attacks where the perpetrators were suspected to have come from law enforcement officers themselves, and the other four were cyber attacks. The research aims to find the cause of this problem, which lies in the provisions of the relevant laws and regulations and at the practical implementation level.